HOW TO MOTIVATE HTEI STUDENTS FOR EXTRACURRICULAR RESEARCH ACTIVITIES IN FOREIGN LANGUAGES - Novikova, Ye.; Новикова, Е. Б.; Новікова, Є. Б. (Харьковский национальный автомобильно-дорожный университет, 2017)
The article considers different types of academic and extracurricular student research work. Main incentives for students of any year of study to conduct such a work have been determined. The expediency of using a foreign language as a means of increasing the efficiency of students’ research work has been substantiated.
СРЕДСТВА МОТИВАЦИИ СТУДЕНТОВ ВТУЗОВ К ВНЕАУДИТОРНОЙ НАУЧНО-ИССЛЕДОВАТЕЛЬСКОЙ РАБОТЕ НА ИНОСТРАННЫХ ЯЗЫКАХ
ЗАСОБИ МОТИВАЦІЇ СТУДЕНТІВ ВТНЗ ДО ВИКОНАННЯ ПОЗААУДИТОРНОЇ НАУКОВО-ДОСЛІДНИЦЬКОЇ РОБОТИ ІНОЗЕМНИМИ МОВАМИ
Keywords: motivation; research work; HTEI; extracurricular activities; foreign language; мотивация; научно-исследовательская работа; ВТУЗ; внеаудиторная работа; иностранный язык; мотивація; науково-дослідницька робота; ВТНЗ; позааудиторна робота; іноземна мова; 378.147